2023
DOI: 10.1055/a-2062-0365
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Influence and Gender Are Correlated with Industry Payments to Orthopaedic Sports Surgeons

Abstract: Background: Social media, specifically Twitter, has become an increasingly used tool in academic orthopaedic surgery to help surgeons connect with patients and peers. This study seeks to understand correlations among social medial influence, academic influence, and gender among academic orthopaedic sport surgeons. Methods: A list of all orthopaedic sports surgeons serving as faculty of sports fellowships in the United States was compiled, along with publicly available demographic information. Their h-indices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
(43 reference statements)
3
0
0
Order By: Relevance
“…Consistent with previous studies, 23,25,26 we found a weak positive correlation between the h-index and nonresearch aggregate industry payments. However, we also found a correlation between the h-index and higher earning percentile.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous studies, 23,25,26 we found a weak positive correlation between the h-index and nonresearch aggregate industry payments. However, we also found a correlation between the h-index and higher earning percentile.…”
Section: Discussionsupporting
confidence: 92%
“…22 Together, these data suggest that gender disparities in industry payments to pediatric orthopaedic surgeons may be perpetuated more by payments to a handful of top-percentile male outliers than by the systemic gendered differences in surgeon-industry interactions. 11,24 Consistent with previous studies, 23,25,26 we found a weak positive correlation between the h-index and nonresearch aggregate industry payments. However, we also found a correlation between the h-index and higher earning percentile.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation